Análise da estrutura de interação do web documentário One Millionth Tower: um estudo semiótico - Sylvestre, Helena Schiavoni [UNESP] (2015)
This research aims to examine the interaction rhizomes of the web documentary One Millionth Tower from the perspective of Peirce's semiotics, study is possibilities of interpretations and assume its importance, since this interaction estructure influences directly in the way that interacting users reads the content visualized by him. As one Millionth Tower, as many interactive web documentaries in emergency in cyberspace are adding in its structure concepts resonsible for the paradigm restructuring of audiovisual media in its traditional mold. The purpose of restructuring an audiovisual media in its traditional mold. The purpose of restructuring an audiovisual genre in constant metamorphosi, since its advent, inspires so many changes yet to be executed